Resistance profiling of soybean RILs against yellow mosaic virus and charcoal rot under field conditions - Riya , M; Ankit , P; Payasi, D K; Tripathi, M K; Yogendra , S; Sanjeev , S; Anita, K P; Jayesh , G; Pawan , K A; Shrivastava, M K (Plant Science Today, 2025)
Soybean (Glycine max) is a vital leguminous crop that faces significant yield losses due to an array of biotic stresses, particularly Yellow Mosaic Virus (YMV) and Charcoal Rot (CR). Present investigation aimed to evaluate the putative resistance of 118 soybean genotypes, including 115 Recombinant Inbred Lines (RILs) along with three checks viz., JS 97-52, NRC-37 and JS 335, under natural disease pressure at JNKVV, Jabalpur, Madhya Pradesh., India well known a hotspot centre for both YMV and CR diseases for a long time. The genotypes were assessed at different growth stages and disease severity classified based on standard rating scales. Among the tested genotypes, 19 RILs displayed high resistance to YMV, while 63 were resistant including the check (62 RILs; a JS 97-52 check), 6 moderately resistant, 8 moderately susceptible including check NRC 37, 16 susceptible including the check JS-335 (15 RILs; 1 check) and 6 highly susceptible. For CR disease, 21 RILs were identified resistant, 41 moderately resistant including the check, JS 97-52 (40 RILS; a check), 22 moderately susceptible including checks JS 335 and NRC 37 (20 RILS; 2 checks), 8 susceptible and 26 highly susceptible. Markedly, 29 RILs demonstrated resistance against both YMV and CR diseases, allowing them valuable candidates for incorporation as donor parents. The findings highlighted the genetic variability of genotypes to disease resistance and the aptitude for selecting resistant line (s) for soybean improvement. The identified resistant genotype (s) can be utilized in breeding programmes to develop high yielding, disease resistant cultivar (s), contributing to sustainable production and reduced reliance on chemical disease management strategies.